2015
DOI: 10.1186/s12711-015-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses for meat quality traits in Chinese Erhualian pigs and a Western Duroc × (Landrace × Yorkshire) commercial population

Abstract: BackgroundUnderstanding the genetic mechanisms that underlie meat quality traits is essential to improve pork quality. To date, most quantitative trait loci (QTL) analyses have been performed on F2 crosses between outbred pig strains and have led to the identification of numerous QTL. However, because linkage disequilibrium is high in such crosses, QTL mapping precision is unsatisfactory and only a few QTL have been found to segregate within outbred strains, which limits their use to improve animal performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…Only the nearest genes to the significant SNPs were considered in view of linkage disequilibrium (LD) decay as the distance between marker and QTL increased [2832]. …”
Section: Methodsmentioning
confidence: 99%
“…Only the nearest genes to the significant SNPs were considered in view of linkage disequilibrium (LD) decay as the distance between marker and QTL increased [2832]. …”
Section: Methodsmentioning
confidence: 99%
“…For instance, when we compared our a*, b* and pH 24 data with those described in six additional GWAS studies4629303132 we only found one positional coincidence between the SSC10 (70.6 Mb) genomic region associated with LD a* in the Lipgen population (Table 3) and the SSC10 (72.8 Mb) region identified by Ma et al 4. as associated with the same trait in the semimembranosus muscle of White Duroc × Erhualian F 2 pigs.…”
Section: Resultsmentioning
confidence: 66%
“…These shared regions were: (a*) SSC4 (80–85 Mb)630, SSC6 (17–22 Mb)430, SSC7 (31–32 Mb)431, SSC12 (58–63 Mb)3031, SSC15 (133–136 Mb)303132; (b*) SSC15 (129–133 Mb)3032; and (pH 24 ), SSC3 (15–19 Mb)3031, SSC15 (133–136 Mb)2932. This latter region on SSC15 (133–136 Mb) appeared to be associated with a*, b*, pH 24 , shear force and cook loss in many independent studies29303132 but not in ours. Interestingly, this SSC15 region contains the protein kinase AMP-activated non-catalytic subunit gamma 3 ( PRKAG3 ) gene, whose polymorphism has causal effects on muscle glycogen depletion, a parameter that can have a strong influence on meat quality traits33.…”
Section: Resultsmentioning
confidence: 99%
“…Recent years, the genome sequences and high-density SNP chips are widely used for detection of variations significantly associated to economic traits in livestock (Liu et al 2015; Ma et al 2014; Rubin et al 2012; Rubin et al 2010; Verardo et al 2016). In this study, we found 1,076 potential specific SNPs between the higher and the lower GP group ( File S1–9 ) using the trancriptome sequencing data, which are the potential variations associated to GP-related traits.…”
Section: Discussionmentioning
confidence: 99%